인공지능 국제 과학연구 네트워크 속 중국의 위상 분석 - 은종학; Eun Jong-hak (중국연구, 2020)
The artificial intelligence (AI) has become a key field of scientific research and discussions about the future engine of science and technology-based innovation. Although China is still generally characterized as a latecomer or a developing country, however, she recently shows some signs of catching-up or even surpassing the traditional forerunners or developed countries in the emerging field of AI. Against this backdrop, this paper takes a fresh approach in analyzing the capacity that China has built up in the AI sector. By collecting bibliographic data from the Web of Science and conducting a series of social network analyses, the paper could capture the rising status of China within the international scientific research network in the field of AI. Also, through a stress test, this paper shows the impact from a hypothetical severance of the US-China tie in AI scientific research would not be unilateral against China. A further micro-level exploration of key players in the AI scientific research network reveals the enhanced centrality of the Chinese Academy of Sciences and major Chinese Universities.